Employment of foreign workers in Malaysia: causes and its implication - Nik Mahmod, Nik Ahmad Kamal (2009)
It is indisputable fact that Malaysia is home to a significant number of legal and illegal foreign workers. Phenomena of foreign workers are world over especially in rich and developed countries but developing country like Malaysia is facing similar phenomenon which is the case study of the present research. This research evaluates causes of foreign workers employment, employment terms and conditions, nature of their jobs, and the financial condition of foreign workers in Malaysia and their respective countries. It will also focus on the agency in charge of foreigner’s employment, legal provisions and protection of subject matters while the positive impact of foreign workers and their effects on local workers will also be discussed in the paper. Data and statistics on foreign workers in Malaysia will be included while useful suggestion will be made to improve various aspects of employment of foreign and local workers in Malaysia.